SUDI DESKRIPTIF TEKNIK PENGUASAAN KEMAMPUAN ORIENTASI DAN MOBILITAS MENGGUNAKAN SMARTPHONE BERBASIS ANDROID SISWA TUNANETRA - Syahrin Umami, Alfi (Jurnal Pendidikan Khusus, 2017)
ABSTRACT. Orientation and mobility abilities should be possessed by the blind students so that they could automatically recognize and master the environment where they lived. The technology development to the Smartphone based Android also began to be felt the utilization largely for fulfilling the daily needs by the blind students who could operate and had a Smartphone. The importance of mastering orientation and mobility abilities and supported by the technology progress to the Smartphone made the blind students assisted in mastering orientation and mobility abilities using the Smartphone based Android. The purpose of this research was to describe about (1) the implementation of mastering orientation and mobility abilities technique using the Smartphone based Android to the blind students in SMPLB and SMALB YPAB Surabaya, (2) the problems found to the implementation of mastering orientation and mobility abilities technique using the Smartphone based Android to the blind students in SMPLB and SMALB YPAB Surabaya, and (3) the efforts to solve the problems in implementing the mastering orientation and mobility abilities technique using the Smartphone based Android to the blind students in SMPLB and SMALB YPAB Surabaya. The method of this research was descriptive qualitative. The data was collected by using interview and observation techniques and the data validation test used triangulation technique i.e. joining data from a number of different data collection techniques and data sources which had been existed. To analyze the data, this research used data reduction, data presentation, and making decision. This research result indicated that the implementation of mastering orientation and mobility abilities technique used the Smartphone based Android for the blind students by utilizing the application of Taptap See and Eye-D to orient the environment around and by utilizing the application of online transportation order  to help having mobility in daily activity. However, there were several problems in the implementation either personal problem of blind students or medium factor i.e. Smartphone and the applications. In the efforts to solve the problems, the students of SMPLB and SMALB YPAB Surabaya used the basic technique of orientation and mobility by utilizing the medium such as a stick, to get more information through the other senses which still functioned, and to utilize the information from the normal people around.   Keywords: Orientation and mobility, Smartphone, Android